A review of 105 negligence claims against accident and emergency departments. Issue 4 (July 1997) - Gwynne, A; Barber, P; Tavener, F
Abstract : OBJECTIVE: To examine 105 successive negligence claims against NHS accident and emergency (A&E) departments in the United Kingdom and to highlight risk management points. METHODS: A systematic review of sociodemographic, clinical, and legal issues was conducted on each claim. RESULTS: 54 claims involved the missed diagnosis of a fracture because of failure to x ray or to interpret the films correctly; 27 claims alleged a missed or delayed diagnosis other than fracture and were mainly due to incomplete clinical examination or failure to x ray or to interpret the films correctly; 24 claims alleged clinical mismanagement in the A&E department; in 82 claims (78%) an SHO was allegedly responsible for the mistake. By the end of August 1996, 92 claims (87.6%) had been closed, of which 38 had been settled out of Court and 54 had not been pursued by the patient after disclosure of the records and--where appropriate--a repudiation of liability. Of the 13 claims remaining open, seven are considered to be defensible and six will have to be settled. CONCLUSIONS: SHOs employed in A&E departments need careful training and supervision, with ready access to senior medical advice, both clinical and radiological. Most errors leading to claims appear in retrospect to have been simple failures of history taking, physical examination, interpretation of radiographs, and communication. Poor quality notes imply substandard care. About half the claims were found to be indefensible.